Rancang Bangun Telemedicine Berbasis Web Di Rumah Sakit Citra Husada Jember - Awiera Shalshabila; Atma Deharha; Bakhtiyar Hadi Prakoso; Muhammad Yunus (Indonesian Journal Publisher, 2024)
Citra Husada Jember Hospital has been running telemedicine services. However, in its services, various problems were found, including the results of patient examinations that had not been written into the medical record but were only recorded manually in a special notebook for home care and telemedicine. In addition, the unitary system of telemedicine has not been implemented so that the integration of health services is not valid. This research is aimed at creating a telemedicine system with the framework of Laravel 9 development. The employed development methodology is Waterfall. With a point of view from the patients, receptionist, admin, doctors, nurses, and pharmacists. It is intended that the Telemedicine system will make it simpler for patients to communicate with doctors without having to physically see them. In order to speed up services in the medical record unit, this also makes it simpler for medical record officers to process data and report. A function for doctor consultations in the form of video conferences is the outcome of the growth of telemedicine and is readily available in web-based telemedicine at Citra Husada Hospital Jember which is users don't need to download an additional app in order to conduct video conferences, print medical records electronically, or conduct patient visits via telemedicine services.